Analisis Daya Tarik Bertempat Tinggal di Apartemen Kalibata City - Nidia Budiani Hartanti; Ragil Haryanto (Jurusan Perencanaan Wilayah dan Kota, 2016)
Residents decisions to reside in the apartment as the property assets can not be separated from the pull factors. Whereas in the management requires an understanding of the attractiveness of ideal residential for urban communities. City as one of the superblock apartment in Jakarta, attract a lot of interest since the first stage of construction to the third stage of construction. This study was conducted to examine the main of pull factors that influence occupant resides in Kalibata City Apartement. This research run out by analyzing the housing indicators as the attractiveness which are residential location, accessibility residential, residential rates and occupancy cost, and residential facilities of Kalibata City Apartment. Method of analysis in this study using a quantitative approach with a quantitative descriptive analysis techniques. From this research, it is known that the factor of Kalibata City’s location and accessibility are the main factors that attract occupants in the residence which is influenced by the residents lifestyle. Meanwhile the role of prices and costs as comparative information to assess the quality of residential objectively.